The CHANSE score: a novel clinical tool incorporating the heel drop test for the diagnosis of pediatric appendicitis - Chun, Min Kyo; Park, Jun Sung; Kim, Dahyun; Han, Jeeho; Lee, Jeong-Yong; Lee, Jong Seung; Choi, Seung Jun (Frontiers in Pediatrics, 2025)
BackgroundAcute appendicitis is one of the most common abdominal surgical emergencies in children presenting to the emergency department. Although clinical guidelines emphasize combining symptom characteristics, physical examination findings, and inflammatory markers for accurate diagnosis, pediatric presentations are often atypical and overlap with other conditions. Classic physical signs such as the obturator, psoas, and Rovsing's signs have limited predictive value. The heel drop test has been reported to outperform rebound tenderness in detecting intraperitoneal inflammation, as it is more objective and less susceptible to misinterpretation. However, evidence regarding its diagnostic utility in appendicitis is limited, and its clinical application in pediatric patients has not been specifically examined.ObjectiveTo evaluate the clinical utility of the heel drop test for diagnosing appendicitis in children and to develop a novel clinical scoring system that incorporates this test.MethodsWe conducted a prospective observational study at a tertiary pediatric emergency center between August 2021 and August 2023. Children with suspected appendicitis underwent standardized clinical and laboratory evaluation, including the heel drop test. Variables significantly associated with appendicitis were identified and used to create a new scoring system (CHANSE: CRP elevation, Heel drop test positivity, Anorexia, Nausea or vomiting, Shift to the left, Elevated WBC). Diagnostic performance was assessed and compared with the Pediatric Appendicitis Score (PAS) using ROC analysis.ResultsAmong 142 enrolled children, 84 were diagnosed with appendicitis. A positive heel drop test was significantly more common in the appendicitis group and showed diagnostic performance comparable to cough/percussion/hopping tenderness. The CHANSE score demonstrated superior diagnostic accuracy compared with PAS (AUC 0.794 vs. 0.763, p < 0.001). A CHANSE score ≥3 showed predictive characteristics similar to a PAS cutoff ≥7. Higher CHANSE scores were also associated with complicated appendicitis.ConclusionThe heel drop test is a useful and objective physical examination method for diagnosing pediatric appendicitis. The CHANSE score, which incorporates this test, is a simple and reliable tool with diagnostic performance comparable to or better than PAS. It may also assist in identifying complicated appendicitis and support timely clinical decision-making.